(untitled) (Research, Society and Development, 2022)
This work aims to carry out a bibliographic review on the physical and ergonomic risks in dental practice over the last 5 years. A bibliographic search was carried out in electronic data sources with consolidated profiles in the scientific community: BBO, Pubmed, Lilacs, Medline and Scielo, the data were combined with associations and outcomes of interests. The investigation was carried out using the descriptors obtained by consulting the website of Descriptores en Ciencias de la Salud-DeCS: Odontología, Riesgo, Ergonomía. As for the eligibility criteria for the articles, for the selection of the sources, the inclusion criteria were considered: original articles, available in their entirety, published in Portuguese, English or Spanish, published in the period from 2016 to 2021. 80 scientific articles were identified, 48 were identified to be read in full text, of which 28 were excluded. Finally, the quality and the risk of sesgo of 20 articles were evaluated and chosen for its analysis and discussion in this article. A lack of more holistic ergonomic education has been identified, including the early detection of musculoskeletal disorders, the selection of appropriate seats, preventive strategies and exercises, and it is essential to address modern activities of the pregrade, postgraduate and education continues.